Safety and efficacy of a feed additive consisting of Lactiplantibacillus plantarum NCIMB 30094 for all animal species (Volac International Ltd) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Roberto Edoardo Villa; Giovanna Azimonti; Eleftherios Bonos; Henrik Christensen; Mojca Durjava; Birgit Dusemund; Ronette Gehring; Boet Glandorf; Maryline Kouba; Marta López‐Alonso; Francesca Marcon; et al. (EFSA Journal)
Abstract Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the safety and efficacy of Lactiplantibacillus plantarum NCIMB 30094 as a technological additive (functional group: silage additive) for use in fresh material for all animal species. The additive is intended for use at a proposed minimum concentration of 1 × 109 colony forming units (CFU)/kg fresh plant material. The bacterial species Lactiplantibacillus plantarum is considered by EFSA to be suitable for the qualified presumption of safety approach to safety assessment. The identity of the strain was established and no acquired antimicrobial resistance genes of concern were detected. Therefore, the FEEDAP Panel concluded that the use of the strain as a silage additive is considered safe for all animal species, for consumers of products from animals fed with the treated silage and for the environment. Regarding user safety, the additive consists of a microorganism, and any exposure through skin and respiratory tract is considered a risk. The additive was shown to be irritant for eyes, but not for skin. The FEEDAP Panel concluded that L. plantarum NCIMB 30094 at the proposed inclusion rate has the potential to improve the production of silage from all fresh plant material.